Crustal S-Wave Velocity Structure Beneath the Northwestern Bohemian Massif, Central Europe, Revealed by the Inversion of Multimodal Ambient Noise Dispersion Curves - Ma, Qingbo; Pan, Lei; Wang, Jian-nan; Yang, Zhentao; Chen, Xiaofei (Frontiers in Earth Science, 2022)
The northwestern Bohemian Massif and adjacent areas are a tectonically active region associated with complex geodynamic activities, that manifest as Quaternary volcanism, earthquake swarms in the upper and middle crust, degassing of CO2, and crustal fluid migration. The intricate tectonic evolution and activities of this region reflect the complexity of the crustal structure therein. However, the crustal models derived from previous studies in this area offer different, even contradictory information regarding the existence of a mid-crustal low-velocity zone (LVZ). In this study, we apply the frequency-Bessel transform (F-J) method to extract the fundamental-mode and up to five higher-mode Rayleigh wave dispersion curves from ambient seismic noise data recorded in the study area and perform multimodal ambient noise dispersion curves inversion. The addition of higher-mode dispersion curves enhances the vertical resolution of the velocity structure inversion results. Our models support the view that the general S-wave velocity level of the crust is high within the study area. We detect two S-wave LVZs beneath the study area that are distributed mainly in the middle crust rather than the lower crust, and these LVZs are separated by a high-velocity zone. Considering the results of previous studies in the area, we infer that these S-wave LVZs may be the consequence of crustal fluids, plastic deformation and even partial melting of the felsic middle crust at relatively high crustal temperatures. Furthermore, these S-wave LVZs could be responsible for the origin and foci depth distribution of earthquake swarms. S-wave low-velocity anomalies are also observed in the uppermost mantle beneath the study area. These S-wave models based on the joint inversion of multimodal dispersion curves can provide new references for understanding the tectonic activity and geodynamic evolution of the northwestern Bohemian Massif and adjacent areas.